LHC, Astrophysics and Cosmology - Giulio Auriemma (Acta Polytechnica CTU Proceedings, 2014)
In this paper we discuss the impact on cosmology of recent results obtained by the LHC (Large Hadron Collider) experiments in the 2011-2012 runs, respectively at √s = 7 and 8 TeV. The capital achievement of LHC in this period has been the discovery of a spin-0 particle with mass 126 GeV/c2, very similar to the Higgs boson of the Standard Model of Particle Physics. Less exciting, but not less important, negative results of searches for Supersymmetric particles or other exotica in direct production or rare decays are discussed in connection with particles and V.H.E. astronomy searches for Dark Matter.